Antiretroviral therapy achieved metabolic complete remission of hepatic AIDS related Epstein-Barr virus-associated smooth muscle tumor. Issue 5 (9th September 2022) - Ara, Takahide; Endo, Tomoyuki; Goto, Hideki; Kasahara, Kohei; Hasegawa, Yuta; Yokoyama, Shota; Shiratori, Souichi; Nakagawa, Masao; Kuwahara, Ken; Takakuwa, Emi; Hashino, Satoshi; Teshima, Takanori
Epstein-Barr virus-associated smooth muscle tumor (EBV-SMT) is a rare mesenchymal tumor which occurs in immunocompromised patients. The immune status is an important factor in the treatment of EBV-SMTs, but the efficacy of antiretroviral therapy (ART) is not elucidated in acquired immune deficiency syndrome (AIDS) related EBV-SMTs. Here, we report the first successful case of a 29-year-old man with hepatic AIDS related EBV-SMT treated with ART solely. Positron emission tomography scan was useful for the evaluation of disease status. Recent advances in ART that enables to restore patient's immune status rapidly may change the treatment strategy in AIDS related EBV-SMT.